Cultura e identidade surda no discurso curricular e seus efeitos na docência de professores formados no curso de Letras/Libras - Polo UFSM - Sarturi, Cláudia de Arruda (2013)
The main purpose of this research is to problematize the relationship between the curriculum discourse of the Languages/Libras Course (UFSM Center) and the production of deaf teachers identities in the field of Deaf Education. Such investigation aims at analyzing the articulation between knowledges presented in the curriculum of that course and deaf teachers daily classroom experiences. This research has taken productions from the fields of Cultural Studies in Education and Deaf Studies as theoretical-methodological tools in order to understand how the curriculum has produced the teaching practices of deaf teachers that narrate experiences involved in the articulation between deaf community and deaf education. The empirical corpus of this research consists of three sets of materials: interviews with Libras deaf teachers, questionnaire applied to graduates of the Languages/Libras Course (UFSM Center), and the Proposal and Pedagogic Project of the Brazilian Sign Language Teaching Course. This study attempts to contribute to the deaf education area by regarding the forms of constitution of deaf teachers graduated in the Languages/Libras Course that represent their culture, their language and their subjectivity through the possibilities of meaning exchanges with the members of other deaf groups. It is understood that the narratives and experiences involved in Sign Language teaching are produced and conveyed during such meaning exchanges. Hence, deaf educators become producers of deaf difference, thus strengthening their pedagogical experience in the field of deaf education; such effects can be perceived in the deaf teachers education in the Languages/Libras Course. The deaf teachers negotiate, consume and spread different meanings concerning language, culture and identity in the context of inclusion education. Therefore, the deaf are seen as both producers and consumers of deaf culture. Inclusion education policies, regarded from the perspective of this analysis, are understood as a bio-political investment, since they are strategies that control, govern and rule deaf subjects actions and conducts by boosting Libras teachers self-government and self-investment practices.